Green finance transforms developed countries’ green growth: mediating effect of clean technology innovation and threshold effect of environmental tax - Kharuddin, Saira; Wei, Deng; Mohd Ashhari, Zariyawati (ScienceDirect, 2024)
Abstract: Green finance, clean technology innovation (CTI), and environmental tax are all eco-friendly measures for diminishing environmental degradation. Few studies have examined how these variables work together to realize the object of green growth (GG). Therefore, this research aims to examine the role of the above factors in achieving GG by using 28 developed countries from 1995 to 2019. These countries have passed over a time of fast progress at the expense of heavy pollution and hence have moved their emphasis to GG. This paper starts with the construction of the GG index based on entropy-weighted TOPSIS, followed by pooled OLS, fixed effect, random effect, the two-step least-square estimator (2SLS), and the System GMM models for hypothesis testing. From the findings, it is obsense of that: (1) Green finance positively affects GG; the higher the levels of GG, the greater the enhancement of green finance on GG. (2) CTI favorably mediates the impact of green finance on GG, and the mediating effect accounts for 14.06% of the overall effect. (3) Environmental tax has a significant threshold effect on the link between green finance and CTI; when high levels of environmental taxes are maintained, the influence of green finance on enterprises' CTI is greatly strengthened, with an increase of 53%. GG will be further promoted by the advancement of enterprises' CTI. Finally, emerging counties would benefit from this study in designing frameworks of green finance, environmental tax, and CTI policies to achieve GG.